Implementasi Kebijakan Program Pemberdayaan Usaha Kerajinan Noken Mama Papua Di Distrik Wania, Kabupaten Mimika, Provinsi Papua Tengah - Macora, Nur Asdianti D.; Polyando, Petrus; Hutasoit, Imelda (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
Law No. 6/2014 on Villages has provided practical space for a new paradigm in village development inIndonesia. In essence, village community empowerment arises to make the community able to build itself and improveits life because of the existence of a low socio-economic condition, resulting in their inability and ignorance. It is thisinability and ignorance of the community that causes their productivity to decline and the poverty rate in the village toincrease. This study aims to describe the Policy Implementation of the Noken Mama Papua. Craft Business EmpowermentProgram in Wania District, Mimika Regency, Central Papua Province. This research uses the theory of policyimplementation using Edward III's theory, namely the dimensions of communication, resources, disposition andbureaucratic structure. This research uses qualitative research methods with a descriptive approach. The datacollection techniques used are interviews, observations and document studies. The author uses data analysis techniques with the stages of data reduction, data presentation, verification and conclusion drawing which are arrangedtentatively. Based on the research conducted, it is known that the policy implementation of the noken craft businessempowerment program has not been implemented properly, especially from the dimensions of human resources, budgetresources and equipment resources. Then, related to the dimensions of the organizational structure, there is no SOPfor empowering noken craft businesses both in the village government and in the district.